사례 분석을 통한 도서관의 치유프로그램 및 서비스 활성화 방안 연구 - 노영희; 김윤정; Noh, Younghee; Kim, Yoon-Jeong (Chŏngbo Kwalli Hakhoechi, 2020)
Until now, healing programs in libraries have provided services under the theme of reading therapy as part of the reading culture program. The purpose of this study is to suggest a way to revitalize healing programs in libraries. This study derives the types and themes of healing activities and analyzes the healing activities in libraries and similar institutions. As a result, first, the healing content to be treated varies depending on the subject, so it should be applied to the library in consideration of this. Therefore, a treatment program was proposed for infants and children (0-13 years), adolescents (14-19 years), adolescents (20-64 years), and old age (65 years and over). Second, it proposed a way to operate healing programs through linkage with institutions such as libraries and medical institutions that were shown as a result of analysis of the healing program. 지금까지 도서관에서의 치유적 프로그램은 독서문화프로그램의 일부로써 독서치유라는 주제로 한정되어 서비스를 제공해 왔다. 이에 본 연구에서는 도서관에서 치유프로그램의 활성화 방안을 제안하고자 하였다. 이에 치유적 활동의 유형과 주제를 도출하였으며, 도서관과 유사기관에서 이루어지는 치유적 활동에 대해 분석하였다. 그 결과, 첫째, 대상에 따라 다뤄야하는 치유 내용이 달라지므로, 이를 고려하여 도서관에 적용해야 한다. 이에 유·아동기(0-13세), 청소년(14-19세), 청장년기(20-64세), 노년기(65세 이상)에 맞는 치유프로그램을 제안하였다. 둘째, 치유프로그램 분석 결과로 나타난 도서관, 의료기관과 같이 기관들과의 연계를 통해서 치유프로그램을 운영하는 방안을 제안하였다.